2017
DOI: 10.1108/acmm-11-2015-1591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser remelting on surface-interface morphologies, bonding modes and corrosion performances of arc-sprayed Al coating

Abstract: Purpose The purpose of this paper is to provide an experimental basis for studying the effects of laser remelting on the surface modification of arc-sprayed Al coating. Design/methodology/approach A layer of arc-sprayed Al coating on S355 steel was remelted with a CO2 laser, and the surface-interface morphologies, compositions of chemical elements and phases of Al coating were analyzed with scanning electron microscopy, energy disperse spectroscopy and X-ray diffraction, respectively. The effects of laser re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The reduced porosity level of an arc-sprayed aluminium coating was also achieved by Wenming et al, who used a CO laser to re-melt the coating [61]. They also noticed that the re-melting of the coating changed the way the coating adhered to the substrate from mechanical to metallurgical bonding.…”
Section: Effect Of Sealingmentioning
confidence: 78%
“…The reduced porosity level of an arc-sprayed aluminium coating was also achieved by Wenming et al, who used a CO laser to re-melt the coating [61]. They also noticed that the re-melting of the coating changed the way the coating adhered to the substrate from mechanical to metallurgical bonding.…”
Section: Effect Of Sealingmentioning
confidence: 78%
“…Munez et al verified that laser remelting can improve the quality of thermal spraying coating by reducing the coating porosity [5]. Liu et al revealed that, through laster remelting, the bonding of coating-substrate interface shifted from mechanical bonding to metallurgical bonding, and the coating had a stronger corrosion resistance [6]. Probing into the damage mechanism of TBCs after laser remelting, Fan et al concluded that the coating damages are related to the surface morphology and segmented cracks [7].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion studies usually focus on industrial standards of salt spraying tests and cyclic accelerated corrosion tests, 9 the load-bearing mechanical properties and the speed of corrosion. There are reports on the corrosion of sacrificial coatings, [10][11][12] and the "corrosion resistance" of the S355 steel through the rust surface coverage and electronic impedance of the steel rather than the surface chemical speciations. 13 Importantly the simulation tests are conducted over relatively long time periods (days, years, if not decades).…”
mentioning
confidence: 99%